Rate of Renal Graft Function Decline After One Year Is a Strong Predictor of All‐Cause Mortality. Issue 3 (11th January 2013) - Moranne, O.; Maillard, N.; Fafin, C.; Thibaudin, L.; Alamartine, E.; Mariat, C.
Abstract : The slope of GFR associates with an increased risk for death in patients with native CKD but whether a similar association exists in kidney transplantation is not known. We studied an inception cohort of 488 kidney transplant recipients (mean follow‐up of 12 ± 4 years) for whom GFR was longitudinally measured by inulin clearance (mGFR) at 1 year and then every 5 years. Association of mGFR at 1 year posttransplant and GFR slope after the first year with all‐cause mortality was studied with a Cox regression model and a Fine and Gray competing risk model. While in Crude analysis, the mGFR value at 1 year posttransplant and the rate of mGFR decline were both associated with a higher risk of all‐cause mortality, only the slope of mGFR remained a significant and strong predictor of death in multivariate analysis. Factors independently associated with a more rapid mGFR decline were feminine gender, higher HLA mismatch, retransplantation, longer duration of transplantation, CMV infection during the first year and higher rate of proteinuria. Our data suggest that the rate of renal graft function decline after 1 year is a strong predictor of all‐cause mortality in kidney transplantation. Abstract : In an incipient cohort of 488 transplant kidney recipients with a mean follow‐up of 12 years, inulin‐derived GFR slope beyond the first anniversary of transplantation appears to be an independent predictor of all‐cause mortality; one that is stronger than a fixed GFR value measured at one year posttransplant.